2021
DOI: 10.1007/s12033-021-00373-0
|View full text |Cite
|
Sign up to set email alerts
|

Production of scFv, Fab, and IgG of CR3022 Antibodies Against SARS-CoV-2 Using Silkworm-Baculovirus Expression System

Abstract: , caused by SARS-CoV-2, is currently spreading around the world and causing many casualties. Antibodies against such emerging infectious diseases are one of the important tools for basic viral research and the development of diagnostic and therapeutic agents. CR3022 is a monoclonal antibody against the receptor binding domain (RBD) of the spike protein (S protein) of SARS-CoV found in SARS patients, but it was also shown to have strong affinity for that of SARS-CoV-2. In this study, we produced large amounts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…F(ab') 2 are produced through the enzymatic cleavage of immunoglobulins and conserve both the antigenbinding region and part of the hinge region. The use of monoclonal F(ab') 2 for the treatment of SARS-CoV-2 has already shown efficacious potential in various studies utilizing different methods to raise the particle (8)(9)(10). However, one important caveat of monoclonal antibodies that extends to most current F(ab') 2 is that they are designed to target one specific epitope, rendering treatment inefficacious in the event of mutation.…”
Section: Introductionmentioning
confidence: 99%
“…F(ab') 2 are produced through the enzymatic cleavage of immunoglobulins and conserve both the antigenbinding region and part of the hinge region. The use of monoclonal F(ab') 2 for the treatment of SARS-CoV-2 has already shown efficacious potential in various studies utilizing different methods to raise the particle (8)(9)(10). However, one important caveat of monoclonal antibodies that extends to most current F(ab') 2 is that they are designed to target one specific epitope, rendering treatment inefficacious in the event of mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Codon optimization. High Five/ExpiSf9/silkworm larvae Affinity chromatography scFv, Fab, IgY and IgG antibody productions [ 94 , 95 , 97 , 98 ] Spike protein and receptor binding domain Signal peptide and peptide tag added. Biotinylation.…”
Section: Application Of Baculovirus Expression Vector System (Bev) Fo...mentioning
confidence: 99%
“…A monoclonal antibody against RBD, CR3022, has been produced using a silkworm-baculovirus expression vector system in three formats (scFv, Fab, and IgG) [ 95 ]. The affinity of the antibody towards S protein was equivalent to the one that was produced in the mammalian expression system.…”
Section: Application Of Baculovirus Expression Vector System (Bev) Fo...mentioning
confidence: 99%
“…Therefore, by evaluating the neutralizing activity of antibodies, SPR assays proved their utility to target viral surface proteins and inhibit SARS-CoV-2 spike interaction with its receptor. The binding of scFv, Fab, and IgG (immunoglobulin G) of CR3022 antibodies to the RBD of SARS-CoV-2 has also been investigated by SPR in a silkworm-baculovirus expression system [56]. SPR analysis demonstrated that the IgG antibodies produced by silkworms had almost the same affinity to S protein that those produced in mammalian expression system.…”
Section: Spr Biosensors As Diagnostic Tools To Detect Neutralizing Antibodiesmentioning
confidence: 99%